Roda Putar Efikasi Diri dan Video terhadap Efikasi Diri Pasien Kanker Payudara - Maulida, Mutia Nadra; Wahyuni, Dian; Usfidalia, Serly (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the comparison of health education through the Wheel of Self-Efficacy (ROPEDI) and videos on increasing the self-efficacy of breast cancer patients. The method employed is Quasi-Experimental with a pre and post-test design involving a control group. The research results indicate a p-value of 0.02, demonstrating a significant change in self-efficacy values across all three groups. Further analysis tests (post hoc) showed that there was a change in the average value in the Rotating Wheel of Self-Efficacy (ROPEDI) group (26.08), the educational video group (25.67) and the control group (20.17). In conclusion, there is an influence of the Wheel of Self-Efficacy (ROPEDI) media and videos on increasing the self-efficacy of breast cancer patients. Keywords: Self-Efficacy, Breast Cancer, Self-Efficacy Spinning Wheel, Video